2011
DOI: 10.1373/clinchem.2010.158014
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Improves Risk Stratification in Patients with Ischemia and Normal Cardiac Troponin I Concentrations

Abstract: BACKGROUND:We assessed the ability of myeloperoxidase (MPO) to identify the risk for major adverse cardiac events (MACE) in patients who present with ischemic symptoms suggestive of acute coronary syndrome and have a normal cardiac troponin I (cTnI) value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Systemic concentrations of MPO have been reported to predict prospective clinical risk in patients who present for assessment of chest pain of suspected cardiac etiology (30) . The current findings use an assay cleared by the FDA and extend observations from early reports from investigators who used a research-grade MPO assay (28, 30) , as well as building on subsequent studies demonstrating the incremental prognostic value of a single measure of plasma MPO compared with cardiac troponin measurements (34) , to suggest that serial monitoring of MPO concentrations provides incremental ability to predict the risk of cardiovascular events. The present observations also confirm previous findings of a rapid increase in MPO concentrations in patients presenting with acute coronary syndromes (35) .…”
Section: Discussionsupporting
confidence: 72%
“…Systemic concentrations of MPO have been reported to predict prospective clinical risk in patients who present for assessment of chest pain of suspected cardiac etiology (30) . The current findings use an assay cleared by the FDA and extend observations from early reports from investigators who used a research-grade MPO assay (28, 30) , as well as building on subsequent studies demonstrating the incremental prognostic value of a single measure of plasma MPO compared with cardiac troponin measurements (34) , to suggest that serial monitoring of MPO concentrations provides incremental ability to predict the risk of cardiovascular events. The present observations also confirm previous findings of a rapid increase in MPO concentrations in patients presenting with acute coronary syndromes (35) .…”
Section: Discussionsupporting
confidence: 72%
“…In individuals with chest pain MPO concentrations at presentation of patients were predictive of major adverse coronary events after 30 days and 6 months [10,22]. In another study [29] the authors reported that MPO levels predicted short-term risk of major adverse coronary events even in patients with normal cardiac TnT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in a subsequent study by the same author regarding the clinical utility of MPO for the risk stratification in patients with ischemia, suggestive of ACS and with normal cTnI concentrations at admission, MPO was a powerful predictor of MACE. The combined use of cTnI and MPO identified a significantly greater proportion of patients at risk of MACE during the 30-day follow-up, however when these markers were considered separately, the adjusted HR for MACE was significantly higher for troponin 104 . A reliable assessment of this study is hampered by the lack of information of the heparin administration before or at the time of admission, which is known to significantly affect the concentration of MPO 105,106 .…”
Section: Role Of Mpo In Patients With Acute Chest Painmentioning
confidence: 88%